2009
DOI: 10.1007/s00261-009-9544-5
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of colonic involvement in endometriosis: double-contrast barium enema vs. magnetic resonance imaging

Abstract: DCBE is more accurate than unenhanced MRI in the diagnosis of bowel endometriosis, and should be preferred in the preoperative management of this disease, since it usually enables a proper surgical planning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(44 citation statements)
references
References 30 publications
0
43
0
1
Order By: Relevance
“…On the other hand, in a prospectively enrolled series of 65 women, Faccioli et al [17] reported a lower MRI accuracy for detection of bowel endometriosis (sensitivity 71.1%, specificity 83.3%, PPV 93%, NPV 46.8% and accuracy 74.6%) compared with double-contrast barium enema (sensitivity 84.7%, specificity 93.7%, PPV 98%, NPV 62.5% and accuracy 86.6%). In this study, MRI was performed within 2 h of the enema to take advantage of the residual colon distension without intravenous contrast medium; however, in this protocol, a dedicated distension of the bowel was not performed for MRI and a lower grade of distension might be postulated for the distal colonic loops as most lesions not detected with MRI were located in the sigmoid colon and caecum (5 and 2 lesions respectively).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…On the other hand, in a prospectively enrolled series of 65 women, Faccioli et al [17] reported a lower MRI accuracy for detection of bowel endometriosis (sensitivity 71.1%, specificity 83.3%, PPV 93%, NPV 46.8% and accuracy 74.6%) compared with double-contrast barium enema (sensitivity 84.7%, specificity 93.7%, PPV 98%, NPV 62.5% and accuracy 86.6%). In this study, MRI was performed within 2 h of the enema to take advantage of the residual colon distension without intravenous contrast medium; however, in this protocol, a dedicated distension of the bowel was not performed for MRI and a lower grade of distension might be postulated for the distal colonic loops as most lesions not detected with MRI were located in the sigmoid colon and caecum (5 and 2 lesions respectively).…”
Section: Discussionmentioning
confidence: 94%
“…Transvaginal, transrectal and endoscopic-transrectal ultrasound have demonstrated comparably high degrees of accuracy for predicting intestinal involvement; however, their field of view is limited to the rectum and the possibility to assess the depth of rectal wall involvement is still challenging [9][10][11][12][13][14][15][16]. Recent studies on double-contrast barium enema [10,17,18] emphasize its capabilities in predicting colonic involvement, although the experience required by the radiologist is a limitation for this technique. Multi-slice CT enteroclysis allows estimating the depth of bowel infiltration, but raises the problem of radiation exposure for women in their reproductive years [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Intestinal involvement in pelvic endometriosis that cause lumen stenosis can be evaluated by DCBE, which performs better than MRI. Its accuracy was reported at nearly 90% (sensitivity 88% and specificity 93%), with a positive predictive value of 97% [64].…”
Section: Double-contrast Barium Enemamentioning
confidence: 99%
“…Double-contrast barium enema (DBCE) has shown promising results when carried out by expert radiologists in the preoperative evaluation of women with clinically suspected intestinal (rectal, sigmoid, cecal) DIE [64]. It does, however, require a low-residue diet for 1 day before the examination, administration of drugs to empty the colon, and exposure to X-rays The presence of DIE is diagnosed on DCBE when the bowel lumen is narrowed at any level from the sigmoid to the anus (extrinsic mass effect) in association with crenulation of the mucosa, spiculation of contour, or both.…”
Section: Double-contrast Barium Enemamentioning
confidence: 99%
“…Adding water contrast to the rectum during transvaginal ultrasonography may facilitate not only the identification of intestinal endometriotic lesions but also the evaluation of the characteristics of the nodules (size, number, depth of infiltration in the intestinal wall, degree of stenosis of the intestinal lumen) [21][22][23] However, bowel preparation is required before adding water contrast to the rectum. Double-contrast barium enema has been widely used in the past and remains an accurate technique for the diagnosis of bowel endometriosis [24][25][26][27][28][29][30] . Bowel nodules appear as extrinsic masses that are associated with mucosal fine crenulations [26] .…”
Section: Diagnosismentioning
confidence: 99%